2016
DOI: 10.2196/medinform.4514
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Technology on Patient Engagement and Health Behavior Change: A Systematic Review of the Literature

Abstract: BackgroundAdvancements in information technology (IT) and its increasingly ubiquitous nature expand the ability to engage patients in the health care process and motivate health behavior change.ObjectiveOur aim was to systematically review the (1) impact of IT platforms used to promote patients’ engagement and to effect change in health behaviors and health outcomes, (2) behavior theories or models applied as bases for developing these interventions and their impact on health outcomes, (3) different ways of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
163
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 198 publications
(187 reference statements)
3
163
0
4
Order By: Relevance
“…Traditionally, patients have tried to physically obtain medical information from ordinary health professionals (doctors, pharmacists and nurses). However, the expansion and generalization of the use of ICTs has implied a radical change in how we obtain information about health and manage diseases [3,4,5,11,12]. While health professionals continue to be the main source of information about diseases (the first option of 75.5% (462/611) of patients is to turn to their doctor), 61.3% (375/611) (55% in the study by An LC et al [13]) also resort to the Internet for information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, patients have tried to physically obtain medical information from ordinary health professionals (doctors, pharmacists and nurses). However, the expansion and generalization of the use of ICTs has implied a radical change in how we obtain information about health and manage diseases [3,4,5,11,12]. While health professionals continue to be the main source of information about diseases (the first option of 75.5% (462/611) of patients is to turn to their doctor), 61.3% (375/611) (55% in the study by An LC et al [13]) also resort to the Internet for information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, remote monitoring by health professionals is currently one of the least used functions, although it has the greatest potential for use [18][19][20][21] as one in three patients would like to have an app with this feature. Providing a new means of communication through ICTs could offer patients the opportunity to get involved in their disease and assume more responsibility with regards to monitoring their health, thus promoting patient empowerment [5,6,9,22,23]. That is why an easy to use app would prove to be a complete tool for this type of patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 With respect to mobile phones specifically, one meta-analysis of 16 studies showed that mobile phone text messaging led to a significant increase in medication adherence, 15 and a systematic review of Questions pertaining to two features unique to the military system were excluded. seven interventions for cardiovascular disease management found mobile phone applications effective in increasing medication adherence and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it helps fill a need in the literature to better understand implementation of these interventions in complex clinic settings [19].…”
Section: Introductionmentioning
confidence: 99%